Land-use impacts of Brazilian wind power expansion. (21st January 2021) - Turkovska, Olga; Castro, Gabriel; Klingler, Michael; Nitsch, Felix; Regner, Peter; Soterroni, Aline Cristina; Schmidt, Johannes
Abstract: While wind power is a low-carbon renewable energy technology with relatively little land footprint, the necessary infrastructure expansion still has land-related environmental impacts. Brazil has seen more than a ten-fold increase in wind power capacity in the last decade. However, little is known about these impacts of wind power generation in Brazil compared to other world regions, although Brazilian wind power infrastructure is concentrated in the least protected ecosystems that are prone to degradation, desertification and species extinction. This study focuses on land-use impacts of past wind power generation development in four Brazilian federal states, covering 80% of the country's installed capacity. We assessed their spatial installation patterns, associated land-use and land cover change in the period before installation until 2018, and potential alternative installation locations, using a detailed wind turbine location database in combination with a high-resolution land-use and land cover map. In contrast to wind parks built in Europe, we found that 62% of the studied wind park area was covered by native vegetation and coastal sands. Overall, 3.2% of the total wind cluster area was converted from native vegetation to anthropogenic use. Wind parks installed mainly on native vegetation, on average, underwent higher land-use change compared to other wind parks. As Brazil intends to more than double its current wind power capacities by 2029, we explored possibilities to reduce environmental risks due to wind power expansion. We showed that this is feasible by integrating wind parks into human-altered areas, as sufficient wind resources there are available.